2001
DOI: 10.1128/jvi.75.18.8368-8379.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Steps of the Polyomavirus Lytic Cycle

Abstract: Kinetic studies of the accumulation of early and late transcripts, early and late proteins, genomes, and live virus, during the lytic cycle of murine polyomavirus wild-type A2, were carried out in synchronized NIH 3T3 cells released from G 0 by the addition of serum after infection. This first-time simultaneous analysis of all parameters of the virus life cycle led to new insights concerning the transcriptional control at the early-to-late transition. During the early phase, early transcripts were synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…No difference in progression of the infected cells though the cell cycle was observed between WTA2-and mutant-infected cells (data not shown). This was expected since the cell cycle of A2-infected cells does not differ from that of mock-infected cells (11).…”
Section: Resultsmentioning
confidence: 94%
“…No difference in progression of the infected cells though the cell cycle was observed between WTA2-and mutant-infected cells (data not shown). This was expected since the cell cycle of A2-infected cells does not differ from that of mock-infected cells (11).…”
Section: Resultsmentioning
confidence: 94%
“…Although the activation of late gene expression occurs concomitantly with the amplification of HPV DNA, our study indicates that induction of late gene expression is not strictly dependent upon differentiation-dependent viral DNA amplification. A link between productive replication and late gene expression has been shown for SV40, polyomaviruses, and adenoviruses (8,9,27,31,51,53,54), but it was unclear if similar mechanisms functioned in papillomaviruses. Studies with SV40 have suggested repressors negatively regulate late expression and that replication titrates away these factors, allowing for expression of viral capsid genes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Upon differentiation in suprabasal cells, viral DNA amplification is activated, along with late transcription, leading to virion production (23). A link between productive viral replication and late gene expression has been well documented in other DNA tumor viruses such as simian virus 40 (SV40) (53,54), polyomavirus (8,9,27,31), and adenoviruses (51), but it is not clear if this extends to papillomaviruses.…”
mentioning
confidence: 99%
“…Similar control may be exerted upon DNA replication during the viral life cycle. DNA replication of many small DNA tumor viruses switches from a uniquely theta mode to rolling-circle replication, perhaps to improve replication efficiency (6,16,22,64) and to enhance late RNA synthesis (12). Inhibition of initiation at the viral origin for theta mode replication by repressors such as mSin3B might facilitate such switching.…”
Section: Discussionmentioning
confidence: 99%